2009
DOI: 10.1093/intqhc/mzp047
|View full text |Cite
|
Sign up to set email alerts
|

Impact and preventability of adverse events in Spanish public hospitals: results of the Spanish National Study of Adverse Events (ENEAS)

Abstract: In Spanish hospitals, AEs associated with health care cause distress, disability, death, lengthen hospital stay and cause increased consumption of health-care resources. A relatively high percentage of AEs in Spain may be preventable with improvements in medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
4
19

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 21 publications
4
87
4
19
Order By: Relevance
“…Numerous studies in different countries have been conducted using this approach in the last years. These studies revealed adverse event rates of 5-15% of all acute care hospital admissions [4][5][6][7][8] . Approximately 50% of events were deemed preventable [5] .…”
Section: Health Care As a Risk: The Magnitude Of The Safety Problemmentioning
confidence: 99%
“…Numerous studies in different countries have been conducted using this approach in the last years. These studies revealed adverse event rates of 5-15% of all acute care hospital admissions [4][5][6][7][8] . Approximately 50% of events were deemed preventable [5] .…”
Section: Health Care As a Risk: The Magnitude Of The Safety Problemmentioning
confidence: 99%
“…31 In stage 2, using the modular review form 2 (MRF2), doctors trained in the use of a standard set of questions analyse positively screened records in detail to determine whether or not they contain evidence of an AE. The basic method has been followed in all the major epidemiological studies, 14,16,[32][33][34][35][36][37][38][39] although there have been modifications to the review form and data capture methods. 30 Previous work in a UK setting, 16,24 assessing the sensitivity of the two-stage review process, reported a sensitivity of 92% and a specificity of 62%.…”
Section: Retrospective Case Note Reviewmentioning
confidence: 99%
“…14,16,[32][33][34][35][36][37][38][39] The study groups all made sequential changes to the original form by adding or subtracting questions, but maintaining the basic format. Charles Vincent and his group made revisions to the review forms, providing a stronger focus on causation and a more tightly structured format after using the tool in a UK setting; this iteration, known as the MRF2, 30,31 is the one used in the study and found in Appendix 1.…”
Section: The Review Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most adverse event reporting systems (with a few exceptions) are designed to be used by health care providers rather than consumers. 2 See Aranaz-Andrés, Aibar-Remó, Vitaller-Burillo, et al, 2009;Baker, Norton, Flintoft, et al, 2004;Brennan, Leape, Laird, Herbert, Localio, et al,, 1991;Michel, Quenon, Djihoud, Tricaud-Vialle, de Sarasqueta, 2007;Thomas, Studdert, Burstin, et al, 2000;Vincent, Neale, and Woloshynowych, 2001;Wilson, Runciman, Gibberd, Harrison, and Hamilton, 1996. 3 See The Health Foundation, undated; World Health Organization, undated; Institute for Healthcare Improvement, 2001.…”
Section: Introductionmentioning
confidence: 99%